The Use of Diagnostic Test for Islamic Education Subject in The Affective Domain Assessment - Fajri Ismail (Ta'dib: Jurnal Pendidikan Islam, 2023)
The affective domain is one of the abilities that is difficult to measure in learning, mainly because it is difficult to find the proper assessment technique. This article described about the the use of diagnostic assessment for measuring students’ affective learning outcomes in Islamic Religious Education subject. The research was conducted at SD Negeri 85, Palembang. The method used in this research was quantitative method. The sample for this research was 25 sixth-grade students. Data were collected by using diagnostic test and observation. The data analysis technique used was quantitative descriptive analysis, in which the results of the diagnostic tests obtained from 25 students were scored and then calculated using descriptive statistics on each assessment indicator and percentages. The results showed that the highest ability in students’ affective domain was in the willingness to accept indicator with the result of 99% and the lowest in the belief indicator with the result of 53%. Therefore, diagnostic tests could be used to measure the learning outcomes of Islamic Religious Education (PAI) in the affective domain.